Sub-part-per-trillion test of the Standard Model with atomic hydrogen - Lothar Maisenbacher; Vitaly Wirthl; Arthur Matveev; Alexey Grinin; Randolf Pohl; Theodor W. Hänsch; Thomas Udem (Nature, 2026)
Abstract Quantum electrodynamics (QED), the first relativistic quantum field theory, describes light–matter interactions at a fundamental level and is one of the pillars of the Standard Model (SM). Through the extraordinary precision of QED, the SM predicts the energy levels of simple systems such as the hydrogen atom with up to 13 significant digits 1 , making hydrogen spectroscopy an ideal test bed. The consistency of physical constants extracted from different transitions in hydrogen using QED, such as the proton charge radius r p , constitutes a test of the theory. However, values of r p from recent measurements 2–7 of atomic hydrogen are partly discrepant with each other and with a more precise value from spectroscopy of muonic hydrogen 8,9 . This prevents a test of QED at the level of experimental uncertainties. Here we present a measurement of the 2S–6P transition in atomic hydrogen with sufficient precision to distinguish between the discrepant values of r p and enable rigorous testing of QED and the SM overall. Our result ν 2S–6P = 730,690,248,610.79(48) kHz gives a value of r p = 0.8406(15) fm at least 2.5-fold more precise than from other atomic hydrogen determinations and in excellent agreement with the muonic value. The SM prediction of the transition frequency (730,690,248,610.79(23) kHz) is in excellent agreement with our result, testing the SM to 0.7 parts per trillion (ppt) and, specifically, bound-state QED corrections to 0.5 parts per million (ppm), their most precise test so far.